Letter from Edwin Montell to James Curtis Booth, December 15, 1866 - Montell, Edwin (1866)
Letter of thanks from Edwin S. Montell to James Curtis Booth (1810-1888). Booth notes on the verso of that he is "selling a little gold" for Montell.
Keywords: Booth, James Curtis, 1810-1888